AMR mechanisms in L. interrogans serovars: a comprehensive study - Petakh, Pavlo; Kamyshnyi, Oleksandr (Frontiers in Cellular and Infection Microbiology, 2024)
Antimicrobial resistance (AMR) is one of the global health challenges of the 21st century. Data regarding AMR mechanisms in Leptospira interrogans, the causative agents of leptospirosis, have been relatively limited. Therefore, our study aimed to identify resistance genes and explore potential resistance mechanisms specific to particular serovars. We conducted a comprehensive analysis of 98 Leptospira strains, representing 10 common serovars, using whole-genome sequencing (WGS) FASTA files. Employing the PATRIC tool from the Bacterial and Viral Bioinformatics Resource Center (BV-BRC), we scrutinized the genomes for AMR genes. Our investigation revealed 32 genes associated with AMR, with 20 key genes consistently prevalent across most strains. Notably, we identified unique efflux pump systems in serovar Pomona, indicating distinctive resistance mechanisms in this serovar. In summary, our findings shed light on the genetic landscape of AMR in Leptospira, uncovering both common and serovar-specific resistance elements. The presence of unique efflux pump systems in serovar Pomona introduces a novel dimension to our understanding of resistance mechanisms. These insights underscore the importance of tailored intervention strategies and collaborative efforts between human and veterinary healthcare professionals, as well as environmental scientists, to address the complex dynamics of leptospirosis and its implications for antibiotic resistance.